Pengembangan Budaya Religius (Religious Culture) di Madrasah: Strategi Membentuk Karakter Bangsa Peserta Didik - Mutohar, Prim Masrokan (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article proposes strategies to build the nation character of students. It follows three stages. The first is socializing the accepted religious values to be implemented in the school. The second is implementing the values systematically for all components in the school. The third is giving rewards for those successfully implementing them. The strategies are done by education practitioners through providing examples, forming good habits, encouraging, and rewarding. In addition, forming religious values at school can be conducted through power strategy, persuasive strategy, normative re-educative strategy.